Fire and fury : inside the Trump White House - Wolff, Michael, 1953- (London : Little, Brown, 2018)
Michael Wolff tells the story of the stormy first nine months of Donald Trump's term as President. Among the revelations: What President Trump's staff really thinks of him -- What inspired Trump to claim he was wire-tapped by President Obama -- Why FBI director James Comey was really fired -- Why chief strategist Steve Bannon and Trump's son-in-law Jared Kushner couldn't be in the same room -- Who is really directing the Trump administration's strategy in the wake of Bannon's firing -- What the secret to communicating with Trump is -- What the Trump administration has in common with the movie The Producers.
Prologue : Ailes and Bannon -- Election day -- Trump Tower -- Day one -- Bannon -- Jarvanka -- At home -- Russia -- Org chart -- CPAC -- Goldman -- Wiretap -- Repeal and replace -- Bannon agonistes -- Situation room -- Media -- Comey -- Abroad and at home -- Bannon redux -- Mika who? -- McMaster and Scaramucci -- Bannon and Scaramucci -- General Kelly -- Epilogue : Bannon and Trump.
Includes index.
AAL, Residential Campus
R K Corporation
Keywords: Trump, Donald, -- 1946-; Bannon, Stephen K; Presidents -- United States; Presidents -- United States -- Staff; United States -- Politics and government -- 2009-2017.; United States -- Politics and government -- 2017-